Digestive and carcass indicators of Rhode Island Red chickens, which intake processed Mucuna pruriens, in two rearing systems. Technical note - Martínez, Madeleidy; Sarrmiento, L.; Santos, R. H.; Herrera, Magaly; Londres, Y (Cuban Journal of Agricultural Science, 2022)
Digestive and carcass indicators are studied in Rhode Island Red chickens in two rearing systems. A total of 120 animals were used, which intake a diet with 15 % of processed Mucuna pruriens, distributed according to a completely random design. Two treatments were established: rearing in captivity and free, with grazing on native vegetation. A total of 30 birds per treatment were sacrificed. The carcass, gastrointestinal tract, gizzard, and empty small and large intestines were weighed. The weight of the small and large intestine increased 0.72 g/kg of live weight in the animals that had free access to grazing. The rest of the indicators did not differ between treatments. It is concluded that the free rearing of Rhode Island Red chickens, which intake processed Mucuna pruriens, modifies the organ related to fiber digestion. This is due to the intake of native vegetation, and does not influence on carcass yield. Key words: birds, captivity, free, treated mucuna, gastrointestinal tract, carcass yield